Potensi Sektor Pertanian Dan Pengaruhnya Terhadap Penyerapan Tenaga Kerja di Provinsi Aceh - Safrida Safrida; Noratun Juliaviani; Anwar Deli; Latifa Isma (JSEP (Journal of Social and Agricultural Economics), 2022)
An increase will follow the increase in population in an area in the rate of increase in the labor force. This will develop problems caused by the lack of functioning of various sectors so that the readiness of employment opportunities is not commensurate with the population growth rate. With the agricultural sector, people can get food as their basic need. The potential of the agricultural sector can be seen from the value of exports, the area of ​​agricultural land, and the wages of the agricultural sector. The purpose of this study is "Analyze the Potential of the Agricultural Sector and Its Effect on Labor Absorption in Aceh Province". This study uses multiple linear regression analysis. Based on the estimation results, it is found that the value of exports, the area of ​​agricultural land, and the wages of the agricultural sector have a positive and significant effect on employment in Aceh Province. This means that any increase in the value of agricultural exports, the area of ​​agricultural land and wages in the agricultural sector will increase the absorption of labor in Aceh Province.